Item, Document, Carrier : An Object Oriented Approach - Manzanos, Norberto (2012)
I discuss the concept of Item as stated by the International Federation of Library Associations and Institutions (IFLA) in the conceptual model Functional Requirements for Bibliographic Records (FRBR) and the object-oriented version of it (FRBR OO). Using object-oriented modeling techniques I analyze the relationship of the Item with the Manifestation entity, the concept of Document, and the physical object as a Carrier of a Content. A class scheme is proposed, not only as an implementation example, but as a way of clarifying some bibliographic concepts as well.
Keywords: Object orientation; Object technology; Objects paradigm; FRBR; Conceptual models; Catalogación; Descripción bibliográfica; Reglas de catalogación